Does PAD and microcirculation status impact the tissue availability of intravenously administered antibiotics in patients with infected diabetic foot? Results of the DFIATIM substudy - Fejfarová, Vladimíra; Jarošíková, Radka; Antalová, Simona; Husáková, Jitka; Wosková, Veronika; Beca, Pavol; Mrázek, Jakub; Tůma, Petr; Polák, Jan; Dubský, Michal; Sojáková, Dominika; Lánská, Věra; et al. (Frontiers in endocrinology, 2024)
AIMS/HYPOTHESIS: The aim of this substudy (Eudra CT No:2019-001997-27)was to assess ATB availability in patients with infected diabetic foot ulcers(IDFUs)in the context of microcirculation and macrocirculation status. METHODS: For this substudy, we enrolled 23 patients with IDFU. Patients were treated with boluses of amoxicillin/clavulanic acid(AMC)(12patients) or ceftazidime(CTZ)(11patients). After induction of a steady ATB state, microdialysis was performed near the IDFU. Tissue fluid samples from the foot and blood samples from peripheral blood were taken within 6 hours. ATB potential efficacy was assessed by evaluating the maximum serum and tissue ATB concentrations(Cmax and Cmax-tissue)and the percentage of time the unbound drug tissue concentration exceeds the minimum inhibitory concentration (MIC)(≥100% tissue and ≥50%/60% tissue fT>MIC). Vascular status was assessed by triplex ultrasound, ankle-brachial and toe-brachial index tests, occlusive plethysmography comprising two arterial flow phases, and transcutaneous oxygen pressure(TcPO2). RESULTS: Following bolus administration, the Cmax of AMC was 91.8 ± 52.5 μgmL-1 and the Cmax-tissue of AMC was 7.25 ± 4.5 μgmL-1(P<0.001). The Cmax for CTZ was 186.8 ± 44.1 μgmL-1 and the Cmax-tissue of CTZ was 18.6 ± 7.4 μgmL-1(P<0.0001). Additionally, 67% of patients treated with AMC and 55% of those treated with CTZ achieved tissue fT>MIC levels exceeding 50% and 60%, respectively. We observed positive correlations between both Cmax-tissue and AUCtissue and arterial flow. Specifically, the correlation coefficient for the first phase was r=0.42; (P=0.045), and for the second phase, it was r=0.55(P=0.01)and r=0.5(P=0.021). CONCLUSIONS: Bactericidal activity proved satisfactory in only half to two-thirds of patients with IDFUs, an outcome that appears to correlate primarily with arterial flow.
Keywords: peripheral arterial disease; Male; infection; intravenózní podání; antibiotic; antibakteriální látky; Aged; mužské pohlaví; senioři; Diabetic Foot; lidé; ženské pohlaví; Anti-Bacterial Agents; Humans; microdialysis; mikrocirkulace; diabetic foot; Administration, Intravenous; Female; Microcirculation; lidé středního věku; Middle Aged; diabetická noha